2021
DOI: 10.1021/acs.inorgchem.1c00284
|View full text |Cite
|
Sign up to set email alerts
|

Postsynthetic Modification of Metal–Organic Frameworks by Vapor-Phase Grafting

Abstract: A vapor-phase grafting strategy is developed for the postsynthetic modification of metal−organic frameworks (MOFs). On the basis of the Schotten−Baumann reaction between acyl chloride (−COCl) and amino (−NH 2 ) groups and hydrolysis of −COCl, the carboxylated MOFs could be prepared through simple exposure in vaporized acyl chloride molecules and immersion in water. The modified MOFs have well-maintained crystalline structures and porosities and show substantially improved fluoride removal performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Previous works have demonstrated that functionalized groups on the surface of metal‐organic frameworks produce a strong binding effect on the guest molecules [154] . DeCoste et al.…”
Section: Application Of Mofs In Industrial Waste Gas Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works have demonstrated that functionalized groups on the surface of metal‐organic frameworks produce a strong binding effect on the guest molecules [154] . DeCoste et al.…”
Section: Application Of Mofs In Industrial Waste Gas Treatmentmentioning
confidence: 99%
“…Previous works have demonstrated that functionalized groups on the surface of metal-organic frameworks produce a strong binding effect on the guest molecules. [154] DeCoste et al further propose that the strong removal of chlorine from NH 2 À UiO-66 is facilitated by the electrophilic substitution reaction during adsorption. However, the HCl byproducts from this chemisorption lead to the collapse of the MOF microstructure.…”
Section: Halogens and Its Compounds Removalmentioning
confidence: 99%
“…Through simple immersion in water, the MOF grafted with acyl chloride groups was transformed into a carboxylated material with high porosity and improved fluoride removal performance. 58 Vapor-phase metalation can be conducted in MOFs by ALD, which can deposit metals or metal oxides on the uncoordinated nodes of MOFs with high density (Figure 3e). 59 This approach breaks the limitation of metal-containing precursor solubility and shows potential in catalyst preparation.…”
Section: Functionalization Of Mofsmentioning
confidence: 99%
“…(d) Schematic illustration of postsynthetic functionalization of MOFs by vapor-phase grafting. Reproduced from ref . Copyright 2021 American Chemical Society.…”
Section: Vapor-phase Postsynthetic Functionalization Of Mofsmentioning
confidence: 99%
See 1 more Smart Citation